Archivführer Schleswig-Holstein. Archive und ihre Bestände - Landesarchiv Schleswig-Holstein; Verband schleswig-holsteinischer Kommunalarch (Veröffentlichungen des Landesarchivs Schleswig-Holstein, 2011)
This publication gives an overview of archives in Schleswig-Holstein is available for the first time in 15 years. The guide concentrates on the official and publicly accessible archives of municipalities, churches and the country, but also lists some private archives. It contains descriptions of more than 150 archives and related institutions. All archives are presented with details of addresses, opening hours, contact persons, internet presence, finding aids and technical equipment. In addition, information is provided on the history of the archive, the area of responsibility (spray), and there is an overview of the archived documents with information on the scope and duration.Furthermore, the volume offers valuable information for working in archives.